The Influence of Leadership Style and the Implementation of E-Performance on Employee Performance at the South Sumatra Provincial Education Office - Muhammad Ridwan; Bukman Lian; Syaiful Eddy (International Journal of Social Science and Humanity, 2025)
This study aims to analyze the influence of leadership style and the implementation of e-performance systems on employee performance at the Provincial Education Office of South Sumatra. Employee performance is a crucial element in achieving organizational goals, while leadership style and e-performance systems are considered key factors influencing success. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to employees, with samples determined randomly. The results indicate that leadership style has a positive but not significant effect on employee performance. Leaders who can motivate and involve subordinates in decision-making tend to enhance employee productivity. The implementation of e-performance systems also has a positive impact on performance, especially through transparency and efficiency in performance evaluation. Simultaneous analysis shows that leadership style and e-performance systems together contribute significantly to improving employee performance, with a coefficient of determination of 67%. However, the study also identifies challenges such as a lack of technological understanding among employees and inadequate infrastructure. Therefore, it is recommended to enhance technical training and ensure the availability of supporting facilities to optimize the implementation of e-performance systems. This research provides practical implications for the leadership of the Education Office in improving managerial strategies and human resource management.